Technological assessment of different solar-biomass systems for hybrid power generation in Europe. (February 2017) - Hussain, C.M. Iftekhar; Norton, Brian; Duffy, Aidan
Abstract: Solar Tower (ST), Parabolic Trough (PT), Linear Fresnel (LF) and Solar Photovoltaic (PV) are discussed in the context of their suitability for hybridisation with biomass in Europe. Technologies, climate data and economic performance have been studied to identify the key drivers of system selection in the choice and design of large scale solar-biomass hybrid power plants. In Europe only one solar-biomass hybrid power plant 'Termosolar Borges' is currently operating in Spain which uses PT technology due to its overall moderate performance characteristics and relatively easy installation. European climate condition where average yearly direct normal irradiance (DNI) can be as high as 1400–1800 kWh/m 2 are suitable for CSP hybridisation. However, the seasonal distribution of solar energy justifies the integration of biomass to ensure power output over the winter months.